Joining the Team: A Case Study Identifying and Assessing Critical Factors Influencing NCAA Division III Student-Athlete Matriculation - Daniel D. Covell; Marilyn K. Pelosi; Jodi Lemoi (Journal of Applied Sports Management, 2013)
This research sought to understand what factors influence how first-year student-athletes at a National Collegiate Athletic Association (NCAA) Division III institution chose the school to attend in light of the heuristic perspective of bounded rationality, which posits that decision makers are rational in some but not all elements of the decision-making process. Data were assessed for the entire respondent group as well as subgroups based on gender and by amount of non-loan financial aid received by using the principal component analysis and the Mann-Whitney U test. The analysis showed athletic variables such as conference affiliation, quality of opponents, recruiting materials, and quality of the athletic website were important determining factors for the entire population group. This research provides the basis for a model for coaches to use to contact and encourage desired prospects to apply and matriculate.
Keywords: Student-athletes; recruiting; NCAA Division III; decision making; matriculation